Pharmacokinetics and biodistribution of extracellular vesicles administered intravenously and intranasally to Macaca nemestrina. Issue 10 (11th October 2022) - Driedonks, Tom; Jiang, Linglei; Carlson, Bess; Han, Zheng; Liu, Guanshu; Queen, Suzanne E.; Shirk, Erin N.; Gololobova, Olesia; Liao, Zhaohao; Nyberg, Lyle H.; Lima, Gabriela; Paniushkina, Liliia; et al.
Abstract: Extracellular vesicles (EVs) have potential in disease treatment since they can be loaded with therapeutic molecules and engineered for retention by specific tissues. However, questions remain on optimal dosing, administration and pharmacokinetics. Previous studies have addressed biodistribution and pharmacokinetics in rodents, but little evidence is available for larger animals. Here, we investigated the pharmacokinetics and biodistribution of Expi293F‐derived EVs labelled with a highly sensitive nanoluciferase reporter (palmGRET) in a non‐human primate model ( Macaca nemestrina ), comparing intravenous (IV) and intranasal (IN) administration over a 125‐fold dose range. We report that EVs administered IV had longer circulation times in plasma than previously reported in mice and were detectable in cerebrospinal fluid after 30–60 min. EV association with peripheral blood mononuclear cells, especially B‐cells, was observed as early as 1‐min post‐administration. EVs were detected in liver and spleen within 1 h of IV administration. However, IN delivery was minimal, suggesting that pretreatment approaches may be needed in large animals. Furthermore, EV circulation times strongly decreased after repeated IV administration, possibly due to immune responses and with clear implications for xenogeneic EV‐based therapeutics. We hope that our findings from this baseline study in macaques will help to inform future research and therapeutic development of EVs.